SnO2 Layer Treatment with Thioacetamide in Perovskite Solar Cell - Fatemeh Ghasemi; Razieh Keshtmand; Nima Taghavinia (Nanochemistry Research)
The electron transport layer plays a pivotal role in shaping the photovoltaic attributes of perovskite solar cells. SnO2 stands out as an exemplary electron transport layer for perovskite solar cells due to its exceptional carrier mobility, deep conduction band, suitable band gap, and compatibility with low-temperature processing. Although surface modification of SnO2 has yielded noteworthy enhancements in device performance over recent years, there remains considerable untapped potential to further refine its efficiency and long-term stability. In this study, thioacetamide was employed to modify the SnO2 surface, aiming to elevate the quality of the electron transport layer and establish a robust interface with perovskite. The findings underscored that the thioacetamide-modified SnO2 layer exhibited augmented perovskite absorption in the visible spectrum compared to the control sample. Additionally, the attenuation in photoluminescence intensity within the modified sample alludes to improved electron extraction and enhanced charge transport from the perovskite layer to the electron transport layer. Assessment of solar cell performance unveiled superior and more consistent photovoltaic parameters in the modified sample. Ultimately, the best efficiency was achieved with the perovskite solar cell using SnO2 modified with thioacetamide, boasting an efficiency of 15.15%